Antibiotic prophylaxis and infection prevention for endoscopic endonasal skull base surgery: Our protocol, results, and review of the literature. (January 2018) - Johans, Stephen J.; Burkett, Daniel J.; Swong, Kevin N.; Patel, Chirag R.; Germanwala, Anand V.
Highlights: Endoscopic endonasal skull base surgery (EESBS) provides minimally invasive corridors to intracranial lesions. The use of antibiotic prophylaxis for patients undergoing EESBS is quite variable. Our antibiotic prophylaxis protocol led to low rates of postoperative meningitis. Dural reconstruction has added to low rates of CSF leaks and infection. Possible changes to our protocol would be to decrease the duration of prophylaxis. Abstract: Endoscopic endonasal approaches to the skull base provide minimally invasive corridors to intracranial lesions; however, enthusiasm for this new approach is always tempered by the recognition that this route requires passage through a nonsterile sinonasal corridor. Despite an increasing number of patients undergoing these surgeries, there remains no consensus on the use of perioperative antibiotics. A retrospective review of consecutive patients undergoing endoscopic endonasal skull base surgery (EESBS) at Loyola University Medical Center by the same neurosurgeon and otolaryngologist team between February 2015 and October 2016 was performed. Antibiotic regimens, presence of an intraoperative or postoperative cerebrospinal fluid (CSF) leak, dural reconstruction method, and rates of sinusitis, meningitis, and/or intracranial abscess were analyzed. 39 patients who underwent a total of 41 EESBSs with a mean age of 46 years were identified. A vascularized nasoseptal flap was used for dural reconstruction when high flow CSF leaks were encountered intraoperatively (n = 17); otherwise, reconstruction mostly consisted of allografts and/or free mucosal grafts. There were zero postoperative cases of CSF leaks, meningitis, or intracranial infection. Our current antibiotic prophylaxis protocol coupled with the use of variable dural reconstruction techniques dictated by intraoperative findings has led to low rates of postoperative CSF leaks, intracranial infections, and meningitis. A survey was also distributed to Neurological Surgery Residency Programs to gain a better understanding of the EESBS protocols that are being used nationally. The practice of antibiotic prophylaxis for patients undergoing EESBS is quite variable and this study should provide the impetus for multi-institutional comparison studies.